In vitro toxicity of fibrous glaucophane. (30th April 2021) - Gualtieri, Alessandro F.; Zoboli, Alessandro; Filaferro, Monica; Benassi, Monia; Scarfì, Sonia; Mirata, Serena; Avallone, Rossella; Vitale, Giovanni; Bailey, Mark; Harper, Martin; Di Giuseppe, Dario
Highlights: Fibrous glaucophane is a mineral species analogous to carcinogenic amphibole asbestos. In vitro toxicity and genotoxicity of fibrous glaucophane has been demonstrated. Fibrous glaucophane exposure led to ROS release and cell injury. The precautionary approach when dealing with glaucophane-rich rocks is recommended. Abstract: The health hazard represented by the exposure to asbestos may also concern other minerals with asbestos-like crystal habit. One of these potentially hazardous minerals is fibrous glaucophane. Fibrous glaucophane is a major component of blueschist rocks of California (USA) currently mined for construction purposes. Dust generated by the excavation activities might potentially expose workers and the general public. The aim of this study was to determine whether fibrous glaucophane induces in vitro toxicity effects on lung cells by assessing the biological responses of cultured human pleural mesothelial cells (Met-5A) and THP-1 derived macrophages exposed for 24 h and 48 h to glaucophane fibres. Crocidolite asbestos was tested for comparison. The experimental configuration of the in vitro tests included a cell culture without fibres ( i.e., control), cell cultures treated with 50 μg/mL ( i.e., 15.6 μg/cm 2 ) of crocidolite fibres and 25-50−100 μg/mL ( i.e., 7.8−15.6–31.2 μg/cm 2 ) of glaucophane fibres. Results showed that fibrous glaucophane may induce a decrease in cell viability and an increase in extra-cellular lactate dehydrogenase release in the tested cell cultures in a concentration dependent mode. Moreover, it was found that fibrous glaucophane has a potency to cause oxidative stress. The biological reactivity of fibrous glaucophane confirms that it is a toxic agent and, although it apparently induces lower toxic effects compared to crocidolite, exposure to this fibre may be responsible for the development of lung diseases in exposed unprotected workers and population.